A Rare Case of Myelodysplastic Syndrome with Ring Sideroblasts, SF3B1 and TET2 Mutations in a Patient with Beta Thalassemia Trait - Ahlstedt, MD, Jeffrey; Wang, MD, PhD, Yanhua; Fang, MD, PhD, Yanan (North American Journal of Medicine and Science, 2017)
Concurrent myelodysplastic syndrome (MDS) and β-thalassemia trait is rare. We reported a case of a 59-year-old man with a known history of β-thalassemia (presumed to be β-thalassemia intermedia) presenting with progressive anemia and worsening fatigue. β-globin mutation analysis revealed a heterozygous mutation in the beta-globin gene, compatible with β-thalassemia trait. Bone marrow biopsy showed erythroid hyperplasia and erythroid dysplasia with increased ring sideroblasts (>15%). Additionally, there is also mild myeloid and megakaryocytic dysplasia. Molecular analysis revealed SF3B1 and TET2 mutations. These findings are consistent with myelodysplastic syndrome with ring sideroblasts (MDS-RS). To the best of our knowledge, this is the first report of MDS-RS with SF3B1 and TET2 mutations in a patient heterozygous for β-globin gene mutation. For β-thalassemia patients with worsening anemia, a comprehensive bone marrow analysis including cytogenetic and molecular studies is important to help further delineate the diagnosis. [N A J Med Sci. 2017;10(1):32-35. DOI: 10.7156/najms.2017.1001032]